Exploring Chinese student’s perceptions of learning management systems: A community of inquiry approach - Li M (MedCrave Group, 2025)
Learning Management Systems (LMS) have become essential platforms for online teaching in higher education, providing spaces for synchronous and asynchronous communication, online interaction, and collaboration. This study investigates the perceptions of Chinese international students regarding their learning experiences in a university course, via an LMS designed based on the Community of Inquiry (CoI) theoretical framework. Twenty Chinese students participated in narrative interviews. The findings indicate overwhelmingly positive perceptions among Chinese students. They expressed satisfaction with the CoI LMS course design, which incorporated techno-pedagogical perspectives and a seamless learning approach. This approach facilitated collaborative, constructive, and meaningful learning in an environment that provided spaces for collaboration, interconnectivity, communication, and learning support. It is recommended to integrate a techno-pedagogical approach in designing LMS course content, structure, organization, communication, and assessment to meet students’ diverse learning expectations.
Keywords: learning management systems (LMS); community of inquiry (CoI); design; collaborative inquiry; seamless learning; techno-pedagogy